The isthmic thyroid nodule: cancer, a myth - Botta, Fernando; Yametti, Luis; Delgado, Bolívar (Cirugía del Uruguay, 1993)
A series of 204 solitary thyroid nodules is analysed in order to determine topography value in cancer risk. lt is concluded that isthmic topography does not presente major risk of malignancy.